1996
DOI: 10.1557/proc-443-155
|View full text |Cite
|
Sign up to set email alerts
|

Diamondlike Carbon Materials as Low-k Dielectrics for Multilevel Interconnects in Ulsi

Abstract: A variety of diamondlike carbon (DLC) materials were investigated for their potential applications as low-k dielectrics for the back end of the line (BEOL) interconnect structures in ULSI circuits. Hydrogenated DLC and fluorine containing DLC (FDLC) were studied as a low-k interlevel and intralevel dielectrics (ILD), while silicon containing DLC (SiDLC) was studied as a potential low-k etch stop material between adjacent DLC based ILD layers, which can be patterned by oxygen-based plasma etchingIt was found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 7 publications
0
41
0
Order By: Relevance
“…There are some experimental techniques for characterization of DLC, for example, Fourier transform infrared spectroscopy (FTIR), high resolution nuclear magnetic resolution (NMR), electron energy loss spectroscopy (EELS), X-Ray Photoelectron Spectroscopy (XPS), Auger spectroscopy, etc. It also has been reported that by either thermal activation 17,18 or low energetic ion irradiations, 19 the structure of the metastable DLC materials will convert some sp 3 bonds to sp 2 bonds towards graphite-like carbon. 11 Thus a fundamental understanding of carbon hybridization under low energetic carbon atom bombardments is of great interest.…”
Section: Introductionmentioning
confidence: 99%
“…There are some experimental techniques for characterization of DLC, for example, Fourier transform infrared spectroscopy (FTIR), high resolution nuclear magnetic resolution (NMR), electron energy loss spectroscopy (EELS), X-Ray Photoelectron Spectroscopy (XPS), Auger spectroscopy, etc. It also has been reported that by either thermal activation 17,18 or low energetic ion irradiations, 19 the structure of the metastable DLC materials will convert some sp 3 bonds to sp 2 bonds towards graphite-like carbon. 11 Thus a fundamental understanding of carbon hybridization under low energetic carbon atom bombardments is of great interest.…”
Section: Introductionmentioning
confidence: 99%
“…In 1997 we reported for the fi rst time low-k DLC fi lms stable up to 400°C [25] and FDLC fi lms with k = 2.3 have been reported elsewhere [27].…”
Section: Properties Of Dlc-type Low-k Dielectrics Dlcmentioning
confidence: 87%
“…Low-k DLC fi lms have been prepared by RF PECVD in a parallel plate reactor, at pressures of 100-300 mTorr and RF powers of 25-100 W, corresponding to power densities of 0.08-0.31 W/cm 2 , as described in detail elsewhere [25,26]. The RF plasma was sustained with a RF power supply at a frequency of 13.56 MHz.…”
Section: Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although many low-k materials in the range of 2.0-4.0 [1][2][3][4][5] have been studied, integration problems and issues like moisture adsorption brought numerous reliability concerns. Methylsilsesquixane ͑MSQ͒ is an attractive candidate for replacement of SiO 2 in future generation ICs because of its inherent low-k ͑2.8͒ and good thermal stability.…”
mentioning
confidence: 99%